Ecology and distribution of mechanically dependent plants along a gradient of past hurricane impact - Batke, Sven Peter (Trinity College (Dublin, Ireland). Department of Botany, 2015)
High energy weather events have been shown to substantially affect forest community dynamics by causing structural and microenvironmental alterations to the affected stand. The degree to which forests respond to storm damage depends on the frequency, intensity and duration of the events and the susceptibility of individual trees to damage. As the microenvironment of forest canopies is closely coupled to the structural environment of the forest (e.g. canopy closure), microclimate alterations are thus likely to follow storm damage.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin